2020
DOI: 10.3390/jcm9092804
|View full text |Cite
|
Sign up to set email alerts
|

Urogynaecological Symptoms among Oncological Survivors and Impact of Oncological Treatment on Pelvic Floor Disorders and Lower Urinary Tract Symptoms. A Six-Month Follow-Up Study

Abstract: It has been widely underlined that both gynaecological malignancies and urogynaecological disorders are often associated with high stress and have a negative impact on the quality of life and psychological well-being of women affected. Knowledge of the pelvic anatomy is crucial in recommending and carrying out the least harmful although successful treatment. Subsequent chemoradiation may also induce or exaggerate troublesome symptoms. The aim of the study was to establish the frequency of urogynaecological sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Following an examination of the titles and abstracts, 51 publications were retrieved in their entirety , with 10 eventually qualifying for this study (Fig. 1) [13][14][15][16][17][18][19][20][21][22]. Most of the studies were retrospective cross-sectional, with the evaluation of PFD taking place at some point following the EC therapy; only 3 of them were prospective, and the overall quality of the studies was poor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following an examination of the titles and abstracts, 51 publications were retrieved in their entirety , with 10 eventually qualifying for this study (Fig. 1) [13][14][15][16][17][18][19][20][21][22]. Most of the studies were retrospective cross-sectional, with the evaluation of PFD taking place at some point following the EC therapy; only 3 of them were prospective, and the overall quality of the studies was poor.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of EC treatment on UI was evaluated in all the studies (n = 10); the impact of EC treatment on POP was evaluated in 4 studies; and the impact of EC treatment on FI was evaluated in 3 studies (Table 1, Ref. [13][14][15][16][17][18][19][20][21][22]). Treatment of endometrial malignancies may include various combinations of surgery, external beam radiotherapy, chemotherapy, and brachytherapy based on the extent of disease and other patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As Ziętek-Strobl and Kozłowski show in their studies, the radicality of surgery affects the patients' life. The effects have been found to depend on the range and extension of the radical operation (16,17) . Radical hysterectomy is associated with multiple complications, the most common of which is impaired bladder voiding function.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, the analysis that was conducted by Ziętek-Strobl et al also indicates the continuation of disorders in the urinary system after oncological treatment, which included surgery and adjuvant treatment, due to endometrial, cervical, vulval, and ovarian cancer, after six months of observation, the number of patients who reported a problem with urinary incontinence increased from 69 to 78. These authors also indicate that the risk of the problem in question occurring is not connected with the type of gynecological cancer, but rather depends on the extent of the surgery [ 42 ]. Because of this, it is indicated that reduced risk surgery should be considered in order to reduce the risk of damaging urogenital nerves and blood vessels [ 43 , 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%